Determination of the crystal structure and photoluminescence properties of NaEu1−xGdx(MoO4)2 phosphor synthesized by a water-assisted low-temperature synthesis technique. Issue 40 (10th May 2017) - Hasegawa, Takuya; Kim, Sun Woog; Abe, Yusuke; Muto, Masaru; Watanabe, Mizuki; Kaneko, Tatsuro; Uematsu, Kazuyoshi; Ishigaki, Tadashi; Toda, Kenji; Sato, Mineo; Koide, Junko; Toda, Masako; et al.
Abstract : Red-emitting NaEu1– x Gd x (MoO4 )2 nano phosphors with high emission intensity were synthesized by a water assisted solid state reaction (WASSR) method, which is a new low temperature synthesis method developed by our research group. Abstract : A single-phase red-emitting NaEu(MoO4 )2 phosphor with nanosized particles was synthesized using a water-assisted solid state reaction (WASSR) method, a new low-temperature synthesis method developed by our group. NaEu(MoO4 )2 exhibits a monoclinic structure with a space group C 2/ c (no. 15), which is composed of a Na/EuO8 dodecahedron with the site occupancy of Na/Eu = 1 : 1 and an MoO4 tetrahedron. To enhance the emission intensity of the NaEu(MoO4 )2 phosphor, Gd 3+ was doped into the Eu 3+ sites and NaEu1− x Gd x (MoO4 )2 (0 < x ≤ 0.50) samples were synthesized using the WASSR method. The emission intensity of the phosphors was successfully enhanced by increasing the Gd 3+ content in the samples with 0 ≤ x ≤ 0.30, but was reduced with x > 0.30. This indicates that the optimum composition of the phosphor for achieving a high emission intensity that is ∼3.8 times higher than that of the NaEu(MoO4 )2 ( x = 0) phosphor is NaEu0.70 Gd0.30 (MoO4 )2 . These phosphors exhibit a granular particle morphology with the particle size of the phosphor being ∼200 nm.